Amplified all-optical polarization phase modulator assisted by a local surface plasmon in Au-hybrid CdSe quantum dots. - Kyhm, K; Je, K; Taylor, R (Optical Society of American (OSA), 2012)
We propose an amplified all-optical polarization phase modulator assisted by a local surface plasmon in Au-hybrid CdSe quantum dots. When the local surface plasmon of a spherical Au quantum dot is in resonance with the exciton energy level of a CdSe quantum dot, a significant enhancement of the linear and nonlinear refractive index is found in both the real and imaginary terms via the interaction with the dipole field of the local surface plasmon. Given a gating pulse intensity, an elliptical polarization induced by the phase retardation is described in terms of elliptical and rotational angles. In the case that a larger excitation than the bleaching intensity is applied, the signal light can be amplified due to the presence of gain in the CdSe quantum dot. This enables a longer propagation of the signal light relative to the metal loss, resulting in more feasible polarization modulation.